2016
DOI: 10.1007/s00464-016-4891-0
|View full text |Cite
|
Sign up to set email alerts
|

Long-term assessment of parastomal hernia prevention by intra-peritoneal mesh reinforcement according to the modified Sugarbaker technique

Abstract: In our series, the incidence of PSH was 7 % and no specific mesh-related complication was noted. Prophylactic mesh reinforcement according to the modified Sugarbaker is an effective technique that addresses the issues related to the occurrence of PSH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…The incidence was 12.5% for those with mesh and 53% for controls with no difference in mesh-related morbidity. Further studies using a synthetic prosthesis with a minimum follow-up of 1 year have shown contradictory results, varying from effective prevention of PSH [28, 29] to unexpected misfortunate outcomes with a high frequency of PSH in the mesh group assessed both clinical and radiologically [26, 30, 31]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence was 12.5% for those with mesh and 53% for controls with no difference in mesh-related morbidity. Further studies using a synthetic prosthesis with a minimum follow-up of 1 year have shown contradictory results, varying from effective prevention of PSH [28, 29] to unexpected misfortunate outcomes with a high frequency of PSH in the mesh group assessed both clinical and radiologically [26, 30, 31]. …”
Section: Discussionmentioning
confidence: 99%
“…Using this technique enlargement of the orifice created in the center of the mesh and augmentation of the extent of the abdominal fascia aperture favoring development of PSH was reported [29]. This technique was described as the “keyhole technique” as opposed to the “modified Sugarbaker technique” [14, 28] in which a non-slit covering mesh is used to correct the PSH.…”
Section: Discussionmentioning
confidence: 99%
“…The recurrence rate after parastomal hernia repair was found to be lower with the Sugarbaker technique than with the keyhole technique [51]. In a trial by López-Cano et al, this new technique showed promising results with regard to the prevention of parastomal hernia [28, 52]. Further RCTs should be performed to confirm the effectiveness of this new technique.…”
Section: Discussionmentioning
confidence: 99%
“…ObS represent 80% of the publications in biomedical journals, independent of the database indexing and eventual impact factor of each journal ( 24 ). Most of the studies we found on PH prevention with mesh in the context of laparoscopic approach were observational and relating to end-colostomy construction in an elective setting ( 12 19 ). Apart from the inherent methodologic limitations of ObS that generate bias ( 25 ), the studies we found comprise a limited number of patients (143 patients), and the results related to laparoscopic approach are indirect, because six of eight studies ( 12, 15 19 ) combined the open and laparoscopic approach.…”
Section: End-colostomymentioning
confidence: 99%
“…Most of the studies we found on PH prevention with mesh in the context of laparoscopic approach were observational and relating to end-colostomy construction in an elective setting ( 12 19 ). Apart from the inherent methodologic limitations of ObS that generate bias ( 25 ), the studies we found comprise a limited number of patients (143 patients), and the results related to laparoscopic approach are indirect, because six of eight studies ( 12, 15 19 ) combined the open and laparoscopic approach. Regarding mesh position, the studies are heterogeneous: in three studies the mesh position is an intraperitoneal onlay (IPOM) with a gap in the middle of the mesh (Keyhole) ( 12 , 14, 18 ), in two a retromuscular position with a keyhole mesh ( 13 , 17 ), in two an IPOM modified Sugarbaker technique ( 15 , 19 ), and in one study the authors use their own mesh position they call SMART ( 16 ).…”
Section: End-colostomymentioning
confidence: 99%